2016
DOI: 10.1080/03019233.2016.1253447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen content on the microstructure and mechanical properties of a cast nickel-base superalloy

Abstract: The effects of nitrogen content on the microstructure and the mechanical properties of a cast nickel-base superalloy (CNS) have been investigated experimentally. Experimental results demonstrated that the grain structure of CNS samples was refined by increasing the nitrogen content, but the area percentage of microporosity has been augmented with increased nitrogen content. Increasing the nitrogen content resulted in the morphology evolution of carbide from an acicular or 'Chinese hieroglyphs' type to blocky o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A typical example is N, which is a grain refiner. The feeder of the 100% sample shows a more marked ''skin effect'': surface grains are smaller than those at the core probably due to N effect, which tends to be accumulated in the feeding systems and refines grains 24,27 . Figure 5 illustrates the macrostructure of the samples.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A typical example is N, which is a grain refiner. The feeder of the 100% sample shows a more marked ''skin effect'': surface grains are smaller than those at the core probably due to N effect, which tends to be accumulated in the feeding systems and refines grains 24,27 . Figure 5 illustrates the macrostructure of the samples.…”
Section: Resultsmentioning
confidence: 98%
“…Due to the higher amount of C and mainly N, that nitrides and carbonitrides could not be dissolved during solution annealing and remain trapped in the matrix causing its embrittlement. 24,27 . The mechanical tests performed in this study on this specific alloy (CW6MC) showed that if the revert proportion is more than 30%, it will slightly influence the mechanical properties of materials.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3, the firstorder interaction coefficients of e j i [34][35][36] were used to calculate the activity coefficient by Eq. (8).…”
Section: Precipitation Model Of Tin Inclusionsmentioning
confidence: 99%
“…[5][6][7] The formation of nonmetallic inclusions was generally caused by the addition of revert alloy, oxidation, and the precipitation during the solidification process. Guo et al 8) reported the contents of oxygen and nitrogen in revert nickel-based superalloys were usually higher than those in the master alloy under the contamination of mold and furnace environment. In order to manufacture high-purity products, a variety of techniques have been developed to remove inclusions from superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen has consistently emerged as one of typical gaseous impurity elements in nickel-based super-alloys that generally imparts negative influences on mechanical properties of these alloys [1][2][3][4]. In particular, small amounts of nitrogen can be very deleterious [5].…”
Section: Introductionmentioning
confidence: 99%